Blood molecular profile to predict genotoxicity from exposure to antineoplastic drugs - Ladeira, Carina (2023)
Funding Information: This work was supported by Instituto Politécnico de Lisboa under grant IDI&CA/IPL/2021/PLASCOGEN_ESTeSL, IDI&CA/IPL/2017/GenTox/ESTeSL, and by the Fundação para a Ciência e a Tecnologia, Portugal, under grant DSAIPA/DS/0117/2020. The human biomonitoring had financial support given by Portuguese Authority of Working Conditions (Project reference: 036APJ/09). Funding Information: This work was supported by Instituto Politécnico de Lisboa under grant IDI&CA/IPL/2021/PLASCOGEN_ESTeSL , IDI&CA/IPL/2017/GenTox/ESTeSL, and by the Fundação para a Ciência e a Tecnologia, Portugal, under grant DSAIPA/DS/0117/2020. The human biomonitoring had financial support given by Portuguese Authority of Working Conditions (Project reference: 036APJ/09). Publisher Copyright: © 2023 The Authors